PERFORMANCE OF BACKCROSS INBRED LINES OF RICE (ORYZA SATIVA L.) ACROSS DIFFERENT WATER REGIMES AND THEIR GENOME ANALYSIS - S. RAMCHANDER; M. RAVEENDRAN; S. ROBIN (The Bioscan, 2014)
The present investigation focused to introgress semi-dwarfism (sd1 locus) from TKM 9 (drought susceptible, donor parent for semi-dwarfism) to Norungan (drought resistant, recurrent) background to develop drought resistant genotypes with improved yield under water limited situations. Stability analysis for grain yield of selected BILs performed under three different moisture regimes were analyzed through Eberhart and Russell (1966) model, revealed that both linear and non-linear components was significantly contributed to grain yield. Six backcross inbred lines recorded higher mean yield than the population mean, regression coefficient (b) around unity and deviation from regression (S2d) nearer to zero, which was non-significant. All the BILs were also genotyped for 167 microsatellite (SSR) markers including gene specific markers of sd1 locus to confirm the introgression to drought resistant background of Norungan and the marker data was used to establish Graphical GenoTypes for each stable individuals using GGT ver.2.0. The result indicated that the stable genotypes of BILs recovered most of the genome (above 90 %) from the recurrent parent Norungan which exhibits high adaptability across environments and had useful introgression for sd1 locus which harness semi-dwarfism from the donor parent TKM 9 on chromosome 1 in all identified genotypes responsible for stable and improved grain yield across varied water regimes.